Ordered Arrays of Gold Nanostructures from Interfacially Assembled Au@PNIPAM Hybrid Nanoparticles - Vogel, Nicolas; et al. (Langmuir, 2012)
In this Article, we report on the assembly of hybrid Au@PNIPAM core shell particles at the air/water interface, their transfer onto solid substrates, and the controlled combustion of the organic material to produce arrays of gold nanoparticles. A detailed investigation on the assembly behavior of such soft hybrid colloids at the air/water interface was performed by correlating the surface pressure area isotherms with SEM and AFM images from samples transferred at different surface pressures. The hybrid particles display a complex behavior at the interface, and we could distinguish three distinct phases with varying interparticle spacings at different compression. The transfer process presented enables the decoration of topologically structured substrates with gold nanoparticle arrays, and the order of the initial monolayers is retained in the arrays of inorganic gold nanoparticles. The change in monolayer morphology upon compression can therefore be used to tailor the interparticle distance between approximately 650 and 300 nm without exchanging the colloids. More sophisticated gold nanostructures can be patterned into symmetric arrays using a similar protocol, which we demonstrate for nanostars and nanorods.